Democracy and the “Kingdom of God” - Kainz, H.P. author. aut Link
VIII, 252 p.
Keywords: I. A Dangerous and/or Useful Kingdom? ............ 5 II. Is There a Concept of the Kingdom of God? . . . . .. . 9 III. The Development of the Concept of a Kingdom of God in the Old Testament ................... 15 IV. Is an Apolitical Kingdom of God Possible? ....... 21 V. The Vicissitudes of Theocracy in Israel ........... 27 VI. New Testament Conceptualization of Messianic Fulfillment . . . . . . . . . . . . . . . . . . . . .. . . 37 . . . . . . . . VII. Is an Alternative Messianic Scenario Conceivable? ................... . . . . . . .. . . 43 . VIII. Did Jesus make a Major Mistake? ............. 51 IX. The Dialectics of Christian Interpretation . . . . . .. . . 59 X. Hermeneutical Circle, or circulus vitiosus? ........ 67 XI. Political Milestones: Three Romes, Three Reichs, Three Kingdoms, and a "Holy Roman ." 73 E mplre ................................. . viii XII. Catholic Political Theology: The "Two Cities" and "Two Swords," and Beyond. . . . . . . . . .. . . 83 . XIII. How Visible can a "City of God" be? ......... 101 XIV. Protestant Political Theology: Beyond the "Two Kingdoms" and the "Two Regiments" . . . . .. . . 109 XV. Does Hegelian Political Theology have a Future? . . . . . . . . . . . . . . . . . . . . . .. . . 119 . . . . . . . . . XVI. The Emergence of the Secular Kingdom of God ..................................... 125 XVII. Secularization-a Boon to Mankind? ......... 137 XVIII. Religious Experience, Chosenness, and Political Expression ....................... 145 XIX. Does Democracy need Redefinition? .......... 157 XX. The Dialectics of Democracy ................. 169 XXI. Democracy and the Kingdom of God . . . . . . .. . . 183 XXII. Are Church and State "Mutually Conducive"? .. 195 XXIII. World Federalism and Ecumenical Christianity 205 Conclusion . . . . . . . . . . . . . . . . . . . . . . . .. . . 221 . . . . . . . . . . BIBLIOGRAPHY. . . . . . . . . . . . . . . . . . . . .. . . 225 . . . . . . .